Inhibition of elastase by N-sulfonylaryl beta-lactams: anatomy of a stable acyl-enzyme complex. - Wilmouth, R; Westwood, N; Anderson, K; Brownlee, W; Claridge, T; Clifton, I; Pritchard, G; Aplin, RT; Schofield, C (1998)
beta-Lactam inhibitors of transpeptidase enzymes involved in cell wall biosynthesis remain among the most important therapeutic agents in clinical use. beta-Lactams have more recently been developed as inhibitors of serine proteases including elastase. All therapeutically useful beta-lactam inhibitors operate via mechanisms resulting in the formation of hydrolytically stable acyl-enzyme complexes. Presently, it is difficult to predict which beta-lactams will form stable acyl-enzyme complexes with serine enzymes. Further, the factors that result in the seemingly special nature of beta-lactams versus other acylating agents are unclear-if indeed they exist. Here we present the 1.6 A resolution crystal structure of a stable acyl-enzyme complex formed between porcine pancreatic elastase and a representative monocyclic beta-lactam, which forms a simple acyl-enzyme. The structure shows that the ester carbonyl is not located within the oxyanion hole and the "hydrolytic" water is displaced. Combined with additional kinetic and mass spectrometric data, the structure allows the rationalization of the low degree of hydrolytic lability observed for the beta-lactam-derived acyl-enzyme complex.